Advances in construction and demolition waste recycling : management, processing and environmental assessment - Torgal, Fernando Pacheco; Ding, Yining; Colangelo, Francesco; Tuladhar, Rabin; Koutamanis, Alexander (Woodhead Publishing series in civil and structural engineering., 2020)
Advances in Construction and Demolition Waste Recycling: Management, Processing and Environmental Assessment is divided over three parts. Part One focuses on the management of construction and demolition waste, including estimation of quantities and the use of BIM and GIS tools. Part Two reviews the processing of recycled aggregates, along with the performance of concrete mixtures using different types of recycled aggregates. Part Three looks at the environmental assessment of non-hazardous waste. This book will be a standard reference for civil engineers, structural engineers, architects and academic researchers working in the field of construction and demolition waste.